2015 IEEE 65th Electronic Components and Technology Conference (ECTC) 2015
DOI: 10.1109/ectc.2015.7159759
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fullerene-C60&C70 on the microstructure and properties of 96.5Sn-3Ag-0.5Cu solder

Abstract: In this study, fullerene nanoparticles (FNSs, a mixture of approximately 80%C60, 20%C70), by varying their weight fractions (0.05, 0.1 and 0.2wt. %) were successfully added into the SAC305 lead free solder to fabricate composite solders through the powder metallurgy processing route. As well as the retained ratios of fullerene reinforcements in the solder joints were firstly tested, the composite solders were also characterized in terms of their microstructure, melting points, electrical conductivity, wettabil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…The refined microstructure also contributed to the enhancement of microhardness value in the composite solder. Besides, Chen et al, [12] also found the addition of fullerene nanoparticles (FNSs) into the SAC305 were able to refine microstructure of the composite solder. The microstructure of SnCu composite lead-free solders was observed by using SEM backscattered image.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The refined microstructure also contributed to the enhancement of microhardness value in the composite solder. Besides, Chen et al, [12] also found the addition of fullerene nanoparticles (FNSs) into the SAC305 were able to refine microstructure of the composite solder. The microstructure of SnCu composite lead-free solders was observed by using SEM backscattered image.…”
Section: Resultsmentioning
confidence: 99%
“…It believed the decreasing size of β-Sn region which has increased the microhardness of composite solder due to the classical dispersion strengthening theory. From that theory, the foreign particles that located in the solder alloy matrix and grain boundaries are likely to change the solder alloy's deformation characteristics by retarding dislocation movement as well as impeding grain-boundary sliding in solder matrix, resulting in enhancement in microhardness [12]. The additional of SiC particles influence the growth and size of the β-Sn region in SnCu-SiC composite lead-free solder.…”
Section: Resultsmentioning
confidence: 99%
“…In the latter, a solder powder and reinforcement are blended by ball milling before compacting, sintering and subsequent extrusion or rolling. However, no matter what method is used, most of the reinforcement added is often excluded outside of the solder joints in the soldering process (Liu et al, 2008;Chen et al, 2015). In such cases, the amount of reinforcement retained in the final solder joints is quite different from the initial one, leading to a reduction in the enhancing effect due to limited doping with the reinforcement.…”
Section: Introductionmentioning
confidence: 99%